Development of a Web-Based Smart Ecosystem Platform for Sustainable Public Service Automation - Shoffan Saifullah; Muhammad Iqbal; Lisnawanty Lisnawanty; Weiskhy Steven Dharmawan; Fahmi Raditya (LPPM Universitas Bina Sarana Informatika, 2026)
Public service delivery in Indonesia continues to face fundamental challenges including inefficient manual administrative processes, error-prone document validation, and the absence of real-time tracking systems. This research aims to develop the PANDU (Pelayanan Publik Digital Terpadu) platform as a web-based smart ecosystem that automates public services sustainably. The platform is built using the Waterfall development method with Model-View-Controller architecture based on Laravel 12 framework, Filament 4.0 administration panel, and Tailwind CSS 4.0 responsive interface. Four main smart features are integrated: automatic document validation, duplicate request detection within a 30-day window, category-based related service recommendations, and automatic priority calculation using multi-criteria scoring algorithm. The platform produces three separate panels for citizens, officers, and administrators, equipped with real-time tracking system through public API and configurable multi-step approval workflows. Black box testing results using equivalence partitioning technique demonstrate one hundred percent functional success rate, while usability evaluation using System Usability Scale yields an average score in the Excellent category with Acceptable acceptability level. The PANDU platform successfully bridges the gap between smart government theoretical frameworks and operational implementation, providing significant contribution to accelerating sustainable digital transformation of public services in Indonesia.